Analysis of the documentary Carlos Cruz, un guanacasteco - Vargas León, Vera Beatriz (2026)
This article analyzes the Costa Rican documentary titled Carlos Cruz, un Guanacasteco by Edgar Trigueros, which is closely tied to the local context of a community in the Nicoya Peninsula. The film frames the land struggle of the late 1970s and the need to engage in dialogue with contemporary socio-economic challenges, such as the lack of roads, river dredging, unemployment, land concentration, and agricultural extractivism. These issues coexist with the ongoing need for community projects in Puerto San Pablo de Nandayure. This reality contrasts with the idealized image of Guanacaste as a land of major tourist attractions, vibrant culture, and environmental diversity; a territory that suffers from significant state and municipal neglect, hindering improvements in human development indicators for both the canton and the province of Guanacaste.